2014
DOI: 10.1159/000365306
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pancreatitis and Pancreatic Cancer

Abstract: Background: Pancreatic cancer (PC) is one of the most lethal diseases with an incidence rate almost equal to the rate of mortality. Chronic pancreatitis (CP) is a common chronic inflammatory disease of unknown etiology that affects the pancreas. Epidemiological studies have identified CP to be a major risk factor for PC. Summary: A greater understanding of the molecular mechanisms linking CP and PC has identified several common pathways that provide targets for future interventions. This article reviews those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 55 publications
(58 reference statements)
1
17
0
Order By: Relevance
“…Based on reports, pancreatic acinar contains a sufficient activity level of Ras, which proves that CP is directly linked with pancreatic cancer [14]. In addition, both pancreatic cancer tissue and CP have same dysregulated signaling pathways, such as nuclear factor kappa B, cytokines, peroxisome proliferator-activated receptor-γ, as well as reactive oxygen species [15]. However, there is possibly no identical genetic susceptibility between pancreatic cancer and CP, at least in the variants with high frequency [16].…”
Section: Discussionmentioning
confidence: 99%
“…Based on reports, pancreatic acinar contains a sufficient activity level of Ras, which proves that CP is directly linked with pancreatic cancer [14]. In addition, both pancreatic cancer tissue and CP have same dysregulated signaling pathways, such as nuclear factor kappa B, cytokines, peroxisome proliferator-activated receptor-γ, as well as reactive oxygen species [15]. However, there is possibly no identical genetic susceptibility between pancreatic cancer and CP, at least in the variants with high frequency [16].…”
Section: Discussionmentioning
confidence: 99%
“…Nonmalignant cells, including adipocytes, constitute a substantial proportion of the tumor mass, and their contents are often correlated with a fast-growing and invasive phenotype. For example, the fibrotic component in some PDAC can occupy more than 90% of the entire tumor mass, and the degree of fibrosis is inversely correlated with the survival prognosis (111). As noncancer cells are common in the TME of all solid tumors, drugs targeting these cells are often used to treat various cancers and produce beneficial effects in human patients.…”
Section: Obese Adipocytes Confer Chemoresistancementioning
confidence: 99%
“…In addition, studies have proven that both acute and chronic pancreatitis are the key risk factors for pancreatic cancer [26][27][28], so we treated 8-week-old KC mice (when PanINs lesions starting formation, as shown in Additional le 1: Fig. S1E) with cerulein to induce pancreatitis, and we found that HSF1 was expressed at a high level and had translocated from the cytoplasm to the nucleus during the pancreatitis ( Fig.…”
Section: Resultsmentioning
confidence: 99%